Best Paper Selection (Yearbook of Medical Informatics, 2019)
Brisimi TS, Chen R, Mela T, Olshevsky A, Paschalidis IC, Shi W. Federated learning of predictive models from federated Electronic Health Records. Int J Med Inform 2018 Apr;112:59-67 https://www.ncbi.nlm.nih.gov/pmc/articles/PMC5836813/Daniel C, Serre P, Orlova N, Bréant S, Paris N, Griffon N. Initializing a hospital-wide data quality program. The AP-HP experience. Comput Methods Programs Biomed 2018 Nov 9 https://www.sciencedirect.com/science/article/pii/S0169260718306242?via%3DihubEstiri H, Stephens KA, Klann JG, Murphy SN. Exploring completeness in clinical data research networks with DQe-c. J Am Med Inform Assoc 2018 Jan 1;25(1):17-24 https://www.ncbi.nlm.nih.gov/pmc/articles/PMC6481389/Sylvestre E, Bouzillé G, Chazard E, His-Mahier C, Riou C, Cuggia M. Combining information from a clinical data warehouse and a pharmaceutical database to generate a framework to detect comorbidities in electronic health records. BMC Med Inform Decis Mak 2018 Jan 24;18(1):9 https://www.ncbi.nlm.nih.gov/pmc/articles/PMC5784648/